It's Time We Talk About Time in Entrepreneurship. (March 2020) - Lévesque, Moren; Stephan, Ute
This editorial draws attention to time to advance entrepreneurship research by focusing on two aspects of time—time perspective and time management. We initiate a deeper conversation on time in entrepreneurship and illustrate the value of a time-based lens for entrepreneurship research through discussing examples at the individual, firm and context levels. These examples consider underdog and portfolio entrepreneurs; well-being; social and unethical entrepreneurial behavior; entrepreneurial teams and entrepreneur–investor dyads; firm strategy; industry and cultural contexts. We review promising methods for time-conscious entrepreneurship research: process, true longitudinal, diary, experience sampling, observational, work-shadowing and time-use studies; historical approaches; experiments; and simulations.